SPEECH ACTS IN JOHN GREEN’S NOVEL “PAPER TOWNS” - Cahyani, Wirna; Sunra, La; Abdullah, Abdullah (Faculty of Languages and Literature, Universitas Negeri Makassar, 2023)
The novel “Paper Towns” in a mystery and young-adult genre tells about Q’s adventures with his friends in his search for Margo. This study aims to identify the types of speech acts that appear in John Green’s novel “Paper Towns”. Speech acts are a subfield of pragmatics that studies how words are used not only to present information but also to perform actions. The theory used is Austin’s theory (1962) where Austin divides into three categories of speech acts: locutionary, illocutionary, and perlocutionary. This study uses a qualitative data analysis method based on Miles, Huberman, and Saldana (2014). The data were taken from John Green’s novel “Paper Towns” and analyzed by reading as much of the novel as possible and trying to understand all the conversations. The researcher categorizes several dialogues that show the types of speech acts in the Paper Towns novel and the meanings of speech acts based on the context of the characters. The results of the study show that the types of speech act in John Green’s novel “Paper Towns” include locutionary, illocutionary, and perlocutionary acts and the meaning of each utterance of the characters in the novel is in accordance with Austin’s theory. The conclusion of this study is that the characters in John Green's novel “Paper Towns” use more illocutionary speech acts in each of their speeches and the meaning of each speech act uttered by the characters in the novel is in accordance with the theory put forward by Austin, where locutionary acts are used by characters to say something according to the true meaning. Illocutionary acts are performed by characters to state or inform something that has an implied meaning and purpose. And perlocutionary acts are used by characters so that the interlocutor obeys the wishes of the character. Keywords: Speech Acts, A Locutionary, An Illocutionary, A Perlocutionary, and Novel